PENGARUH ACADEMIC SUPPORT DAN LINGKUNGAN KELUARGA TERHADAP NIAT BERWIRAUSAHA MAHASISWA - Indri Hastuti Listyawati; Deniyati Zufriah (Universitas Boyolali, 2024)
The aim of this research is to examine the influence of academic support and family environment on students' entrepreneurial intentions in Yogyakarta. This research is quantitative research. The population of this research is all students of the Kumala Nusa College of Business Sciences. Meanwhile, the sampling method uses convenience sampling. The data collection method uses a questionnaire. The total data collected was 49 respondents. Variable measurement uses a Likert Scale. Data analysis uses multiple regression analysis. The results of the analysis show that academic support and family environment influence students' entrepreneurial intentions. The results of this research show that students need to receive support from campus and family. The greater the support received by students, the greater the student's encouragement to become an entrepreneur.